The quiet place - Stewart, Sarah, 1939- (Farrar Straus Giroux, 2012)
The story of young immigrant Isabel, who misses her family and friends back in Mexico while decorating a large box as a place of quiet contemplation and encountering new experiences, including a first snowstorm and a kind teacher.